Epistimologi Hukum Islam - Lubisa, Syarifuddin; Anwar Husein; Uswatun hasanah (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The study of the epistemology of Islamic law is essential to understanding the foundations of knowledge and methodologies underlying the formulation of Islamic legal thought that is rational, contextual, and just. This research arises from the need to re-examine the structure of Islamic legal knowledge to ensure its relevance in facing social transformations and modern challenges. The study employs a qualitative approach using library research methods by examining primary sources such as the Qur’an, Hadith, and classical juristic works, as well as secondary sources from contemporary literature. The literature review reveals that the epistemology of Islamic law rests on three main foundations: bayani (textual), ‘aqli (rational), and ‘irfani (spiritual), each complementing the others in the process of deriving legal rulings (istinbat al-ahkam). The discussion shows that the interaction between revelation and reason produces a legal system that is not only normative but also applicable and adaptive. The analysis of modern Islamic scholars’ perspectives indicates a paradigm shift from a purely textual approach toward an integrative one that incorporates maqasid al-shariah as a guiding principle for understanding the ultimate objectives of Islamic law. The study concludes that the epistemology of Islamic law constitutes a unified system of knowledge that harmonizes revelation, reason, and social reality in order to achieve justice, welfare, and balance in human life.